Back Cover: Cover Image, Volume 74, Issue 10. Issue 10 (11th September 2018) - Pettinga, Dean J; Ou, Junjun; Patterson, Eric L; Jugulam, Mithila; Westra, Philip; Gaines, Todd A
Abstract : The back cover image Kochia scoparia, by Dean J Pettinga et al., is based on the Research Article Increased chalcone synthase (CHS) expression is associated with dicamba resistance in Kochia scoparia, DOI:10.1002/ps.4778 Abstract : The back cover image Kochia scoparia, by Dean J Pettinga et al., is based on the Research Article Increased chalcone synthase (CHS) expression is associated with dicamba resistance in Kochia scoparia, DOI:10.1002/ps.4778